Numerical simulation of tectonic stress field and prediction of fracture target in the Longmaxi Formation, southeastern Chongqing - Xiao Li; Liming Wu; Bingxian Wang; Qiuyuan Hu; Dawei Dong (地质科技通报, 2021)
Shale reservoirs are well developed in Southeast Chongqing, of which the Longmaxi Formation is the main reservoir.Compared with other types of reservoirs, structural fractures are very well developed in this type of shale reservoirs, making this area potential for shale exploration.In this paper, based on the field survey data and typical regional geological sections, structural characteristics of the study area were analyzed.On this basis, a geological model for the shale reservoir was established.In order to restore the process of structural evolution within the study area of the Himalayan period, further, the finite element analysis software Ansys 15.0 are used.Simulation results fit the actual structural development well.Based on the results as well as Griffith fracture criterion and Coulomb-Moore fracture criterion, multiple influencing factors of shale reservoirs were comprehensively analyzed, and comprehensive fracture development coefficient IF were used to quantification of the fractures distribution prediction in shale reservoirs.The larger comprehensive fracture development coefficient IF is, the more developed the shale reservoir fractures would be.Therefore, shale reservoirs in the study area are classified into three categories: fracture favorable zone Type Ⅰ(IF ≥ 3.0, fracture very well developed), fracture favorable zone Type Ⅱ(3.0, 2.0], fracture good developed) and fracture favorable zone Type Ⅲ(2.0, 1.0].